2009
DOI: 10.1590/s0036-36342009000800027
|View full text |Cite
|
Sign up to set email alerts
|

Detección del cáncer de mama en México: síntesis de los resultados de la Encuesta Nacional de Salud Reproductiva

Abstract: Strategies for standardization and quality control for the clinical breast examination are needed to contribute in the prevention and control of breast cancer in Mexico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
18

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 8 publications
0
5
0
18
Order By: Relevance
“…However, coverage of mammography is still limited and most women are diagnosed in a late stage leading to suboptimal survival. [42][43][44] It is agreed upon that incidence and mortality due to cervical cancer has decreased even though estimates differ in terms of absolute numbers. 45,46 Cervical cancer but also breast cancer are paradigm examples of complex regional cancer patterns, which are clearly linked to the level of deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…However, coverage of mammography is still limited and most women are diagnosed in a late stage leading to suboptimal survival. [42][43][44] It is agreed upon that incidence and mortality due to cervical cancer has decreased even though estimates differ in terms of absolute numbers. 45,46 Cervical cancer but also breast cancer are paradigm examples of complex regional cancer patterns, which are clearly linked to the level of deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…También se encontró en la misma encuesta que las mujeres con escolaridad de al menos preparatoria llevan a cabo esta práctica seis veces más frecuentemente que las mujeres sin estudios (23) .…”
Section: Discussionunclassified
“…In 2007, the risk of dying from this disease among women older than 25 years in the State of Mexico was 14.2 deaths per 100,000 women [3]. A Mexican national study published in 2009 found that only 37% of Mexican women performed monthly breast-self examination (BSE) [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer survival depends on early detection and treatment [4]. Attitudes toward breast cancer are crucial determinants of early detection [9], and the Mexican public health system has attempted to increase the use of early detection services by changing women’s attitudes about breast cancer, however, those efforts have not been successful [10].…”
Section: Introductionmentioning
confidence: 99%